Comparative evaluation of photodynamic therapy induced by two different photosensitizers in rat experimental candidiasis - Heidar Khademi; Nakisa Torabinia; Maryam Allameh; Hamid Reza Jebreilamtigh (Wolters Kluwer Medknow Publications, 2014)
Background: Antimicrobial efficacy of photodynamic therapy (PDT) depends on both the photosensitizer (PS) and laser parameters. In the present study, antimicrobial effectiveness of PDT with different concentrations of two PSs was compared. Materials and Methods: In this study, we employed fifty-nine 6-week-old male Wistar rats. All except the negative and overall control groups were immunosuppressed and then orally inoculated with a suspension of Candida albicans (9 × 10 8 CFU/ml). At 4 days after oral inoculation, swabbing of tongue dorsum was performed to recover yeast from the tongue before treatment; on the next day, PDT was carried out on tongue dorsums by use of different concentrations of methylene blue (MB) or poly-L-lysine-chlorine (e6) conjugate (pL-ce6) as PS; followed by a 10 min diode laser illumination at 660 nm (n = 6 each). Then, sampling was again performed. The difference between yeast recovery before and after treatment was compared between the groups by one-way analysis of variance test (α = 0.05). After sacrificing the animals, their tongues were surgically removed and processed for histological evaluation of the presence of yeast and tissue reaction. Results: PDT mediated by both PSs, regardless of the type and their concentration, resulted in a significant microbiological and histological reduction in C. albicans counts in comparison with positive control group (P < 0.001). There was no difference in epithelial lesions and inflammatory responses between groups. Conclusion: PDT mediated MB or pL-ce6 is a promising approach for treatment of oral candidiasis.